“Information Security in the Banking Sector: A Systematic Literature Review on Current Trends, Issues, and Challenges“ - Vasquez Ubaldo, Alfredo Leonidas (2023)
In recent years, information security has become a very important aspect, since it creates serious trouble for organizations that do not take it into consideration. In this regard, it was detected that many entities in the banking sector experience multiple problems that are mainly related to the way in which they protect their data, so it is necessary to pay close attention to this issue. For this reason, in this investigation it was decided to carry out a systematic review of the literature, obtaining 2,787 articles through searches in electronic databases. Likewise, the PRISMA method was used, which allowed the identification of 15 relevant articles to form the synthesis of the investigation. In the same way, a bibliometric analysis was carried out, which allowed knowing the gaps in knowledge. Finally, in the conclusions emphasis is placed on several aspects; for example, it is highlighted that cybercriminals constantly attack the banking sector and it is mentioned that all the research questions posed were successfully answered.